Handwerk in der digitalen Ökonomie Rechtlicher Rahmen für den Zugang zu Daten, Software und Plattformen - Podszun, Rupprecht (Wirtschaft und Recht für Mittelstand und Handwerk, 2021)
If you want to repair a vehicle or a machine today you need access to data and software interfaces. For many craft enterprises, "access" is becoming a key issue in the digital economy. This study identifies the rules that currently determine access to data, platforms and software. It shows that there is a risk that, in the future, digital gatekeepers will decide which companies have access to customers at all. Rupprecht Podszun, a law professor and an expert on competition in the platform economy, presents the current framework and proposals to protect open markets and to put consumers in the driving seat. This book is a valuable resource for everyone interested in the role of law for markets in the data economy.